Anti-porn: the resurgence of anti-pornography feminism - Long, Julia (Zed Books, 2012)
"Anti-porn feminism is back. Countering the ongoing 'pornification' of Western culture and society, with lads' mags on the middle shelf and lap-dancing clubs in residential areas, anti-porn movements are re-emerging among a new generation of feminist activists worldwide. This essential new guide to the problems with porn starts with a history of modern pro and anti political stances before examining the ways in which the new arguments and campaigns around pornography are articulated, deployed and received. Drawing on original ethnographic research, it provides an in-depth analysis of the groups campaigning against the pornography industry today, as well as some eye-opening facts about the damage porn can do to women and society as a whole. This unique and inspiring book explains the powerful comeback of anti-porn feminism, and it controversially challenges liberal perspectives and the mainstreaming of a porn culture that threatens to change the very nature of our intimate relationships"–Résumé de l'éditeur.
Section: 246 p. ; 23 cm
Keywords: approches et analyses; corps; cours; discipline; féminisme anti-porn; féminisme pop; militance; patriarcat; premier cycle; sex1911; sexualité; systèmes d'oppressions; thématiques

Women's Barracks: The original 1950 tale of life and love in the free french army - Torres, Tereska; Mayne, Judith (The Feminist Press at CUNY, 2012)
This novel—based on the author's real-life experiences—is credited as the first candidly lesbian novel, originally published in 1950, that “scandalized mid-century America” (The New York Times).As the Blitz rains down over London, taboos are broken, affairs start and stop, and hearts are won and lost. This account of life among female Free French soldiers in a London barracks during World War II sold four million copies in the United States alone and many more worldwide. Women’s Barracks was banned for obscenity in several states and denounced by the House Select Committee on Current Pornographic Materials in 1952 as an example of how the paperback industry was “promoting moral degeneracy.” In spite of such efforts—or perhaps, in part, because of them—the novel became a record-breaking bestseller and inspired a whole new genre: lesbian pulp.Femmes Fatales restores to print the best of women’s writing in the classic pulp genres of the mid-20th century. From mystery to hard-boiled noir to taboo lesbian romance, these rediscovered queens of pulp offer subversive perspectives on a turbulent era.
Keywords: 1900-1999; 1940-1949; amour interdit; approches et analyses; europe; hétérosexisme; identités LGBTQIA2+; littérature; patriarcat; personnes lesbiennes; pulp lesbien; périodes historiques; royaume-uni; régions géographiques; sexualité; systèmes d'oppressions; thématiques